THE ROLE OF WORK DISCIPLINE IN MEDIATING THE EFFECT OF WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. XYZ - Ega Malinda Angeliza Siahaan; Ida Bagus Ketut Surya (Adisam Publisher, 2025)
The role of work discipline in mediating the effect of work motivation on employee performance is crucial in a company. In the face of globalization and increasing competition, companies are required to understand and optimize these factors to enhance their performance and competitiveness. Therefore, this study aims to analyze the relationship between work motivation, work discipline, and employee performance. The research was conducted at PT. XYZ, with a sample of 71 employees determined using a saturated sampling technique. Data collection was carried out through interviews and questionnaire distribution. The data analysis technique used in this study was path analysis with SPSS. This study aims to analyze the mediating role of work discipline in the effect of work motivation on employee performance. The results show that work motivation and work discipline have a positive and significant effect on employee performance, work motivation has a positive and significant effect on work discipline, and work discipline partially mediates the effect of work motivation on employee performance. The theoretical implication of this study supports previous research findings, while the practical implication for PT. XYZ is to maintain employee performance, work motivation, and work discipline among its employees.